In vitro and in vivo assays of selected plant extracts against fruit rot fungi - Fatin Nabila Shaari,; Nur Ain Izzati Mohd Zainudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Post-harvest losses of crops in Malaysia is estimated at around 20%. Fungal infection is one of the primary causes of post-harvest loss in fruits. The common use of synthetic fungicide to combat fruit rot fungi poses negative impacts on human health and the environment. The objective of this study was to determine the efficacy of selected plant species as a safer alternative for post-harvest treatment. Ethanolic leaf extracts of Piper sarmentosum, Psidium guajava, and Cymbopogon citratus were tested against Fusarium oxysporum from tomato rot, Fusarium proliferatum from banana rot, and Colletotrichum gloeosporioides from mango rot. In vitro analysis was conducted using poisoned food bioassay and the percentage inhibitions of Fusarium oxysporum growth were 93.50% by Piper sarmentosum extract, 46.68% by Psidium guajava extract, and 40.48% by Cymbopogon citratus extract. A test on a different fungus, Fusarium proliferatum, showed that Piper sarmentosum, Psidium guajava, and Cymbopogon citratus extracts displayed percentage inhibitions of 88.78%, 36.66%, and 22.44%, respectively. In vitro test on Colletotrichum gloeosporioides showed that Piper sarmentosum extract inhibited the fungal growth by 96.23%, while Cymbopogon citratus and Psidium guajava extract inhibited the fungal growth by 52.62% and 52.22%, respectively. The mechanism of action of these extracts appeared to be fungistatic. Piper sarmentosum was selected for further analysis by in vivo assay as it displayed the most significant anti-fungal action. The study was conducted using Piper sarmentosum leaf extract of various concentrations (25, 50, 50, and 100 mg/mL). The leaf extract displayed dose-dependent activity, with the highest reduction in disease severity observed at concentration of 100 mg/mL. The findings showed the potential use of Piper sarmentosum, Psidium guajava, and Cymbopogon citratus leaf extract as anti-fungal agent for post-harvest treatment to minimize fruit loss. Piper sarmentosum leaf extract showed comparable inhibitory action to commercial fungicide carbendazim.